2015
DOI: 10.1002/aenm.201501733
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Supported Nitrogen and Boron Rich Carbon Layer for Improved Performance of Lithium–Sulfur Batteries Due to Enhanced Chemisorption of Lithium Polysulfides

Abstract: the charge process, and this is considered to be another factor contributing to the rapid decay of Li-S batteries.Recently, it has been reported that nitrogen-doped carbon exhibits strong chemisorption for polysulfi des and Li 2 S, and consequently longer cycling performance has been achieved by developing N-doped carbon/S composites. [ 10 ] It has been demonstrated that the electronegative N atoms in the carbon matrix are particularly effective in forming S x Li⋅⋅⋅N interactions via the lone-pair electrons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 45 publications
6
117
0
Order By: Relevance
“…3a), which is as good as those reported before293031. Moreover, excellent cyclability over 500 cycles with a small fading rate of 0.08% per cycle at 0.2 C and high coulumbic efficiency above 99% are also achieved.…”
Section: Resultssupporting
confidence: 84%
“…3a), which is as good as those reported before293031. Moreover, excellent cyclability over 500 cycles with a small fading rate of 0.08% per cycle at 0.2 C and high coulumbic efficiency above 99% are also achieved.…”
Section: Resultssupporting
confidence: 84%
“…[36] The peak pattern of the SCNT/S spectrum indicates that the sulfur still appears in the crystalline form, but its peak intensity is weakened, indicating that the sulfur has successfully entered the internal pores of the carbon material. [39] These results show that the one-step atomization doping process has successfully doped nitrogen into the carbon nanotube microspheres, and some nitrogencontaining functional groups have also been formed in the NSCNT/S composites. The sulfur content in the carbon nanotube microsphere/sulfur composite can be determined.…”
Section: Structure and Morphology Characterization Of Carbon Nanotubementioning
confidence: 68%
“…According to the N 1s spectra, the nitrogen contents for N‐ZDC 1 , N‐ZDC 2 , N‐ZDC 3 and N‐ZDC 4 are 3.5, 3.8, 4.1, and 4.2 %, respectively (Figure d). Nitrogen doping could not only improve the surface wettability of a carbon matrix, but also helps to immobilize lithium polysulfides by additional chemical interaction of the N atoms with the polysulfides and consequently further enhances the electrochemical performance …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the conductivity of carbon materials can be enhanced by doping with heteroatom elements, such as N and B . More importantly, strong interactions between Li 2 S n and N atoms in the carbon matrix exist according to density functional theory and diffusion experiments . Hence, the surface adsorption of sulfur species on carbon hosts is largely improved, which in turn allows a reduced lithium polysulfides dissolution and an enhanced sulfur utilization.…”
Section: Introductionmentioning
confidence: 99%